Analisis Minat Belajar Kimia Siswa melalui Penerapan Model Pembelajaran Learning Cycle 5E menggunakan Cerita Misteri pada Materi Asam Basa - Ghufrooni, Rifqi; Darwis, Zulmanelis; Kurniadewi, Fera (LPPM Universitas Negeri Jakarta, 2019)
The interest of students in learning chemistry is one of the factors that increases the learning process that can be improved through Learning Cycle 5e learning and the use of mystery topics in learning. Therefore the purpose of this study is to analyze the interest of chemistry learning students through the application of Learning Cycle 5E using mystery stories to acid-base learning. This study was conducted at SMAN 61 Jakarta in the even semester of the 2018/2019 academic year with the research subjects consisting of 32 people of class XI MIPA 3. The study was conducted using qualitative analysis methods by collecting data through observation, reflective journals, student interviews and interest questionnaire. Learning Cycle 5E learning consists of 5 stages, namely engagement, exploration, explanation, elaboration and evaluation. Mystery Scenario used in the elaboration stage to expand students' understanding and make students interested in learning. The results of the analysis show situational interest, pleasure for the study of chemistry and self-efficacy in chemistry in chemistry formed during learning. Aspects of belief about chemistry and self-concept in chemistry appear only in a few students.The most dominant Learning Cycle 5E stage that raises student interest is Elaboration Keywords Interest in learning chemistry, Learning Cycle 5E, Mystery scenario, acid base